Legal Protection Against Substitute Heirs Based on Islamic Law - Novita Ernila Tisnawati; Sri Budi Purwaningsih (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine and analyze the determination of substitute heirs in the Decision of the Sidoarjo Religious Court Number 1498/Pdt.5/2020/PA.Sda and the Judge's Decision whether to consider the principles of Islamic inheritance law in accordance with the Compilation of Islamic Law on legal protection of substitute heirs. This research method uses a normative research type using a case approach. By collecting data on primary legal materials and secondary legal materials from court decisions and materials related to problems, namely scientific articles, journals. The analysis of legal materials begins through a literature study, which begins with an inventory by collecting the legal rules as a whole by relating to the main issues that exist. As in the case of inheritance rights disputes that occur as a result of one of the heirs not wanting to divide each part by deliberation. So that it can be used as a valid reason to file a dispute. This study concludes that the Sidoarjo Religious Court in deciding cases of inheritance rights disputes, uses Islamic inheritance law as a material consideration that is adapted to the Compilation of Islamic Law to make the decision. In addition, it also uses the principle of balanced justice to determine the share of heirs and substitute heirs.